ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, SERTA HARGA TERHADAP KEPUASAN PELANGGAN THE CORNELIAS THE CORNELIA’S AUTHENTIC FAMILY CUISINE - Rimba Fadha Sendy Perdana; Emmywati (PUTRA JAWA PUBLISHER, 2023)
In the backdrop of economic and technological advancements and the intense global competition in the business world, companies strive to outcompete their rivals by offering customers more satisfactory goods and services at competitive prices. This competition serves a dual purpose of attracting new customers and retaining existing ones. This study aims to investigate the relationship between pricing, product quality, service quality, and overall customer satisfaction. The participants in this study have willingly contributed their time and insights, specifically customers of The Cornelia's Authentic Family Cuisine. A purposive sampling method was employed to select fifty respondents based on specific criteria. In this research, the analytical approach used is multiple linear regression analysis. The research findings reveal that pricing, product quality, and service quality all have a significant and positive impact on the level of customer satisfaction at Cornelia's Authentic Family Cuisine. Consequently, this study establishes a direct correlation between customer satisfaction and the quality of both the product and the service, as well as pricing.